Influence Analysis of Virtual Impedance on the Stability of Parallel System of Inverters with Different Voltage Levels - Wentao MA; Jinmei WANG; Yongqi WANG (Zhongguo dianli)
Using virtual impedance technology to optimize the double closed-loop control structure can improve the equivalent output impedance of the inverter to be inductive and enhance the accuracy of power distribution by traditional inductive droop control strategies in low-voltage micro-grids, thus inhibiting circulating current. This approach, however, tends to overlook the impact of virtual impedance on system stability. In this regard, the transfer function of a three-loop control structure is derived, which includes virtual impedance, line impedance and common point voltage. A parallel model of inverters with different voltage levels is built, considering virtual complex impedance, and the model is simplified with the Thevenin’s equivalent. According to the Nyquist stability criterion, the effect of virtual impedance on system stability is analyzed under various operating conditions. The results show that the multi-inverter parallel system can maintain stable operation after the virtual impedance is added.